If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(y+4)=-2(8y-8)+5y
We move all terms to the left:
7(y+4)-(-2(8y-8)+5y)=0
We multiply parentheses
7y-(-2(8y-8)+5y)+28=0
We calculate terms in parentheses: -(-2(8y-8)+5y), so:We get rid of parentheses
-2(8y-8)+5y
We add all the numbers together, and all the variables
5y-2(8y-8)
We multiply parentheses
5y-16y+16
We add all the numbers together, and all the variables
-11y+16
Back to the equation:
-(-11y+16)
7y+11y-16+28=0
We add all the numbers together, and all the variables
18y+12=0
We move all terms containing y to the left, all other terms to the right
18y=-12
y=-12/18
y=-2/3
| -17+v-20=-3+11 | | 45=16v-7v | | 1x+8=3x+4 | | -12t+20+3t=-20+t | | 14-8x=4x-46 | | 20-4y=-7-y+18 | | 40x+1.5x=1250 | | 3c^2-375=0 | | -7(x-1)-(-8x-8)=-2 | | 5c+7=3c-5 | | 3a+9=7a+5 | | 63+2x=105 | | 3(2x-3)=5(x+5) | | 2/3(y-18)=7 | | 7m=9+4m | | 63=2x=105 | | x-3/5=5 | | 2b+1=5b+10b= | | -9=-5-3a-11 | | a=15=4a-3 | | 7g-8=10g+8-4g | | -4(a+6)=-63 | | -6.5+1.3x=9.1 | | 3y+2=8y+17 | | h/2+h/3=6 | | 7r-8=6r | | 5(3x-8)=-115 | | 7r–8=6r | | 24-16x=72 | | 19u=8+18u | | 2y+6=3y+8y= | | 11b+3=-16+12b |